A Case of Perilymphatic Fistula with Inner Ear Anomaly Diagnosed Preoperatively by the Cochlin-Tomoprotein Detection Test - Kana Lee; Naoki Ochi; Kohei Yamahara; Kunihiko Makino; Tetsuo Ikezono (Case Reports in Otolaryngology)
We present a case of perilymphatic fistula (PLF) with inner ear anomalies having sudden, progressive sensorineural hearing loss and describe the fistula repair surgeries. We focus on the diagnosis methods of PLF and clinical course of PLF with inner ear anomaly. The cochlin-tomoprotein (CTP) detection test is very useful for the surgeons to encourage the earlier operation to sudden hearing loss cases. It is also helpful to define the diagnosis of PLF after operation. We could not get the good result as to hearing from the fistula repair surgery mainly because surgery was held 1 month after the onset. The results of the case, as well as recommendations of other reports, suggest that patients with sudden sensorineural hearing loss and PLF may need repair surgery within at most 2 weeks from the onset. We describe how to diagnose PLF more accurately using CTP detection combined with intraoperative findings.